Individualism versus Collectivism Orientation as Moderator between Co-Workers’ Social Support and Work to Family Enrichment - Kumar, Aneel; Channa, Khalil Ahmed; Maharvi, Muhammad Waqas (Journal of Accounting, Business and Management (JABM), 2018)
The purpose of this study was to test the effect of co-workers’ support on work to family enrichment and the moderating role of individualism/collectivism orientation in the relationship between social support and work to family enrichment. There were 243 respondents of banking sector on which the analysis was based. Primary data were collected through the five point Likert type of survey questionnaire. The findings of this study showed co-workers’ support as the potential antecedent of work to family enrichment. The workplace resource of co-workers’ support engendered the positive experiences of work to family enrichment in the employees. Further, individualism/collectivism orientation was found as the significant moderator in the relationship between co-workers’ support and work to family enrichment. The relationship was stronger for employees high on individualistic/collectivist orientation, as compared to those who were low on such orientation. These results validate the prevalence of collectivist cultural context in this part of world.